Disposable butyronitrile wear-resistant glove and preparation process thereof
By modifying nitrile rubber latex and introducing modified cellulose and amide paraffin to form a multi-component network structure, the problem of poor wear resistance of existing nitrile gloves is solved and the wear resistance of gloves is achieved. Improvement in tensile strength and elongation at break.
Patent Information
- Application Number
- CN202411885324.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-01-21
AI Technical Summary
The wear resistance of existing disposable nitrile gloves is poor, resulting in short wear time and low tensile strength and elongation at break, limiting their use range.
Through the modification of Tinto rubber gel proof, the introduction of modified cellulose and amide gymiped wax, forming a network structure that combines multiple components, improves the wear resistance of gloves, and increases the stretching strength and the elongation rate.
A significant improvement of the wear resistance of Ding Yan gloves, increasing the stretching strength and the elongation of the break, and the service life of the gloves is prolonged and the operation sensitivity is increased.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to disposable nitrile wear-resistant gloves and a preparation process thereof. Background Art
[0002] Nitrile gloves are made of synthetic latex. Compared with natural latex gloves, they are less likely to cause allergies. At the same time, they have good softness, tensile strength, elongation at break, oil resistance and wearing comfort. They can be used to make disposable thin nitrile gloves, lined labor protection gloves and thick nitrile gloves. They have been widely used in medical, housework, electronics, chemical, aquaculture, glass, food and other fields.
[0003] A Chinese patent (publication number CN106397894B) discloses a method for preparing nitrile gloves. The method for preparing nitrile gloves of the invention only requires one chlorine wash, and the chlorine wash is performed before dipping the hand mold, that is, the hand mold is first washed with chlorine before dipping the hand mold, so that the surface of the nitrile gloves formed after dipping is smooth, convenient to wear and non-sticky, and only one chlorine wash greatly reduces the chlorine content of the nitrile gloves and simplifies the processing procedure; at the same time, water washing is used to effectively remove particles and surface ions on the surface of the nitrile gloves, increasing the cleanliness of the nitrile gloves. The wear resistance of disposable nitrile gloves on the market is generally average, resulting in a short wearing time, and the tensile strength and elongation at break are also insufficient; while the wear-resistant flocking gloves have high wear resistance, but their operation sensitivity is poor and they cannot effectively touch electronic screens such as mobile phones and tablets.
[0004] Therefore, how to improve the wear resistance of nitrile gloves while increasing tensile strength and elongation at break by modifying nitrile rubber latex and introducing other effective components has become a key area that needs to be tackled. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a disposable nitrile wear-resistant glove and a preparation process thereof, aiming to solve the problems in the prior art that the disposable nitrile gloves have poor wear resistance resulting in a short wearing time, and at the same time, have low tensile strength and elongation at break resulting in limited use.
[0006] The invention modifies nitrile rubber latex and introduces modified cellulose and amide paraffin at the same time, and effectively improves the wear resistance of nitrile gloves through the joint action of multiple components, and increases the tensile strength and elongation at break.
[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows: The first aspect of the present invention provides a process for preparing disposable nitrile wear-resistant gloves, comprising the following steps: Step S1: adding 2.5 to 2.7 parts of potassium hydroxide, 0.6 to 1.0 parts of sulfur, 2.0 to 3.0 parts of zinc oxide, 0.8 to 1.5 parts of accelerator, 0.6 to 0.8 parts of antioxidant, 0.05 to 0.15 parts of cellulose and 0.05 to 0.08 parts of sodium dodecylbenzene sulfonate to 90 to 100 parts of nitrile rubber latex in parts by weight, stirring for 15 to 20 hours, adding 2.0 to 3.5 parts of anti-wear agent, adjusting the pH to 10.5 to 11.0, and obtaining a latex mixture; Step S2: Mix 20-22 parts of calcium nitrate, 1.5-2.0 parts of a release agent, 0.1-0.3 parts of an alcohol ether auxiliary agent, and 0.2-0.6 parts of a wetting agent by weight, and stir for 6-8 hours at a stirring speed of 15-20 r / min to obtain a coagulant; Step S3: placing the mold in the coagulant at 55-60° C. for a first dipping treatment, drying at 120-125° C. for 1-2 hours, and then placing the mold in the latex mixture for a second dipping treatment; Step S4: vulcanize the mold that has completed the second dipping treatment in a vulcanization oven at 130-135° C. for 20-30 minutes, then use a chlorine lotion to perform a passivation treatment, then perform a chloride ion surface neutralization rinse, and dry to obtain a disposable nitrile wear-resistant glove; The nitrile rubber latex is modified nitrile rubber latex; The preparation method of the modified nitrile rubber latex comprises: adding 20 to 30 parts of carboxyl-terminated nitrile rubber to 80 to 100 parts of toluene by weight and stirring for 20 to 30 minutes, then adding 5 to 10 parts of formic acid and 4 to 8 parts of a hydrogen peroxide solution with a mass concentration of 35% at 10 to 12° C., heating to 30 to 40° C. and reacting for 1 to 2 hours, washing with deionized water to neutrality after the reaction is completed, extracting and separating a toluene layer, adding 1 to 3 parts of sulfur quantum dots to the toluene layer, stirring for 6 to 8 hours, and then rotary evaporating to obtain the modified nitrile rubber latex.
[0008] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0009] As a preferred technical solution of the present invention, the preparation method of the sulfur quantum dots comprises: adding 4 to 6 parts of sodium hydroxide and 3 to 5 parts of polyethylene glycol to 40 to 50 parts of deionized water by weight, stirring evenly, adding 1 to 2 parts of sulfur, and stirring at 70 to 75° C. for 2 to 4 hours to obtain an orange-red solution; using a peristaltic pump to pass air into the orange-red solution and continue to react for 20 to 24 hours, and after the reaction is completed, 10 to 12 parts of a 35% mass concentration hydrogen peroxide solution is added dropwise to react for 40 to 60 minutes, and after the reaction is completed, the solution is cooled to room temperature to obtain a light yellow solution, dialyzed, rotary evaporated, and freeze-dried to obtain the sulfur quantum dots.
[0010] Sulfur quantum dots are introduced into modified nitrile rubber latex. Sulfur quantum dots can serve as additional cross-linking points to promote cross-linking reactions between polymer chains, thereby increasing the cross-linking density of the vulcanization network, obtaining stronger intermolecular bonding forces, and thus improving tensile strength.
[0011] As a preferred technical solution of the present invention, the cellulose is modified cellulose; the preparation method of the modified cellulose comprises: adding 20 to 30 parts of cellulose to 200 to 250 parts of chloroform by weight, stirring for 2 to 4 hours under a nitrogen atmosphere, then adding 6 to 8 parts of furfurylamine and 2 to 4 parts of pyridine, stirring for 6 to 8 hours under a nitrogen atmosphere at 60 to 70° C., centrifuging after the reaction to obtain a reaction product, and vacuum drying to obtain the modified cellulose.
[0012] The modified cellulose introduces a six-membered heterocyclic ring containing a nitrogen atom through pyridine, which can undergo N-cyanation with the polar group cyano in nitrile rubber, increasing the binding force between polymer chains and thus improving the overall wear resistance of the material.
[0013] As a preferred technical solution of the present invention, the anti-wear agent is amidated paraffin; the preparation method of the amidated paraffin comprises: adding 3 to 5 parts of ethylenediamine to 8 to 10 parts of benzenesulfonic acid solution with a mass concentration of 20% by weight, stirring evenly to obtain an amidating agent; mixing 80 to 100 parts of paraffin and 180 to 200 parts of toluene evenly, stirring at 80 to 90°C for 1 to 2 hours, then adding 15 to 20 parts of an amidating agent, stirring and reacting at 95 to 100°C for 2 to 4 hours, and after the reaction is completed, condensing and separating to obtain the amidated paraffin.
[0014] Wax amide paraffin can reduce the cohesive energy between the molecular chains of nitrile rubber, making it softer and more ductile. Through the plasticizing effect, the rubber is easier to deform and less likely to break during stretching, thereby improving the elongation at break of nitrile gloves. Due to the presence of wax amide paraffin, a "soft and hard alternating" microstructure can be formed inside the rubber. When subjected to external pressure or friction, this structure can effectively disperse stress and prevent crack expansion caused by local stress concentration, thereby improving the overall wear resistance.
[0015] As a preferred technical solution of the present invention, the accelerator is accelerator BZ or accelerator EZ.
[0016] As a preferred technical solution of the present invention, the antioxidant is selected from any one of antioxidant CPL, antioxidant 2246, and antioxidant 3052, or a combination of at least two of them.
[0017] As a preferred technical solution of the present invention, the release agent is calcium stearate or magnesium stearate.
[0018] As a preferred technical solution of the present invention, the alcohol ether auxiliary agent is selected from any one of tridecyl alcohol polyether-4, tridecyl alcohol polyether-3, and laureth-4, or a combination of at least two thereof.
[0019] As a preferred technical solution of the present invention, the fingertip thickness of the disposable nitrile wear-resistant gloves is 0.15-0.25 mm.
[0020] The second aspect of the present invention provides a disposable nitrile wear-resistant glove prepared by the process described in the first aspect.
[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention adds a wear-resistant agent, and the wear-resistant components migrate to form a protective wear-resistant layer on the surface of the product during the vulcanization and molding process of the product, so that the wear resistance index can be greatly increased; by adjusting the ratio of the vulcanization system and the proportion of the antioxidant components in the formula, the product is not easy to turn yellow during the high-temperature vulcanization and molding process, and the fingertip thickness of the product is increased and will not age; sodium dodecylbenzene sulfonate is added during the raw material preparation process to improve the chemical stability of the wear-resistant agent in the nitrile latex, so that its effective components are not easy to precipitate during the pre-vulcanization process of the latex.
[0022] (2) The modified nitrile rubber latex of the present invention is treated with formic acid and hydrogen peroxide solution to introduce epoxy groups. The epoxy groups have high reactivity and can react with hydroxyl groups and amino groups in modified cellulose as well as combine with amides in amide paraffin. Together with the cross-linking points provided by sulfur quantum dots, they work together to form a uniform and dense network structure, reduce defects and weak links, avoid stress concentration, and improve wear resistance. At the same time, a high degree of cross-linking can enhance the bonding force between molecules and increase the tensile strength and elongation at break of the nitrile gloves.
[0023] (3) The modified cellulose of the present invention introduces a six-membered heterocyclic ring containing a nitrogen atom through pyridine, which can undergo N-cyanation with the polar group cyano in the nitrile rubber, thereby increasing the binding force between polymer chains and thus improving the overall wear resistance of the material.
[0024] (4) Sulfur quantum dots are introduced into the modified nitrile rubber latex of the present invention. The sulfur quantum dots can serve as additional cross-linking points to promote the cross-linking reaction between polymer chains, thereby increasing the cross-linking density of the vulcanization network, obtaining stronger intermolecular bonding force, and thus improving the tensile strength.
[0025] (5) The amide wax of the present invention can reduce the cohesive energy between the molecular chains of nitrile rubber, making it softer and more ductile. Through the plasticizing effect, the rubber is more easily deformed and less likely to break during the stretching process, thereby improving the elongation at break of the nitrile gloves. Due to the presence of the amide wax, a "soft and hard alternating" microstructure can be formed inside the rubber. When subjected to external pressure or friction, this structure can effectively disperse stress and prevent crack expansion caused by local stress concentration, thereby improving the overall wear resistance. DETAILED DESCRIPTION
[0026] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0027] The sources of some components in the embodiments and comparative examples are as follows: Commercially available nitrile rubber latex, model number X6617, was purchased from Shanghai Xintema Chemicals Co., Ltd.; Potassium hydroxide, CAS No. 1310-58-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Sulfur, CAS No. 7704-34-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Zinc oxide, CAS No. 1314-13-2, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Accelerator BZ, CAS No. 136-23-2, purchased from Jinan Hongteng Weiye New Materials Co., Ltd.; Accelerator EZ, CAS No. 136-94-7, purchased from Hubei Hengjingrui Chemical Co., Ltd.; Antioxidant CPL, CAS No. 68610-51-5, purchased from Hubei Qifei Pharmaceutical Chemical Co., Ltd.; Antioxidant 2246, CAS No. 119-47-1, purchased from Zhongshan Dixin Chemical Co., Ltd.; Antioxidant 3052, CAS No. 61167-58-6, purchased from Zhongshan Dixin Chemical Co., Ltd.; Commercially available cellulose, CAS number 9004-34-6, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Sodium dodecylbenzenesulfonate, CAS No. 25155-30-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Commercial paraffin wax, CAS No. 8002-74-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Calcium nitrate, CAS No. 13477-34-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Calcium stearate, CAS No. 1592-23-0, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Magnesium stearate, CAS No. 557-04-0, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Tridecyl alcohol polyether-4, CAS No. 69011-36-5, purchased from Shanghai Huayuan Century Trading Co., Ltd.; Tridecyl alcohol polyether-3, CAS No. 4403-12-7, purchased from Jiangsu Haolong Chemical Co., Ltd.; Laureth-4, CAS No. 68439-50-9, purchased from Zhengzhou Huiju Chemical Co., Ltd.; Wetting agent, model TEGO245, purchased from Shanghai Huiyan New Materials Co., Ltd.; Sodium hydroxide, CAS No. 1310-73-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Polyethylene glycol, product number 202398, was purchased from Sigma-Aldrich; Hydrogen peroxide solution, product number H433859, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Carboxyl-terminated nitrile rubber, product number A265194, purchased from Zhengzhou Huiju Chemical Co., Ltd.; Toluene, CAS No. 108-88-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Formic acid, CAS No. 64-18-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Chloroform, CAS No. 67-66-3, purchased from Sinopharm Chemical Reagent Co., Ltd.; Furfurylamine, CAS No. 617-89-0, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Pyridine, CAS No. 110-86-1, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Ethylenediamine, CAS No. 107-15-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Benzenesulfonic acid, CAS No. 98-11-3, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0028] Preparation of modified nitrile rubber latex: (1) The preparation method of sulfur quantum dots comprises: adding 6 parts of sodium hydroxide and 5 parts of polyethylene glycol to 50 parts of deionized water by weight, stirring evenly, adding 2 parts of sulfur, stirring at 75°C for 4 hours to obtain an orange-red solution; using a peristaltic pump to pass air into the orange-red solution and continue to react for 24 hours, after the reaction is completed, adding 12 parts of a 35% hydrogen peroxide solution by mass concentration and reacting for 60 minutes, after the reaction is completed, cooling to room temperature to obtain a light yellow solution, dialyzing, rotary evaporation, and freeze-drying to obtain the sulfur quantum dots. (2) In parts by weight, 30 parts of carboxyl-terminated nitrile rubber are added to 100 parts of toluene and stirred for 30 minutes. Then, 10 parts of formic acid and 8 parts of 35% by mass hydrogen peroxide solution are added at 10°C, and the temperature is raised to 30°C for reaction for 2 hours. After the reaction is completed, the mixture is washed with deionized water until neutral, and the toluene layer is separated by extraction. 3 parts of sulfur quantum dots are added to the toluene layer, and the mixture is stirred for 8 hours, and then rotary evaporated to obtain the modified nitrile rubber latex.
[0029] Preparation of modified cellulose: By weight, 30 parts of cellulose are added to 250 parts of chloroform, and stirred for 4 hours under a nitrogen atmosphere. Then, 8 parts of furfurylamine and 4 parts of pyridine are added, and the mixture is stirred for 6 hours at 70° C. under a nitrogen atmosphere. After the reaction is completed, the reaction product is centrifuged and vacuum dried to obtain the modified cellulose.
[0030] Preparation of amidated paraffin: In parts by weight, 5 parts of ethylenediamine are added to 10 parts of benzenesulfonic acid solution with a mass concentration of 20%, and stirred evenly to obtain an amidating agent; 100 parts of paraffin and 200 parts of toluene are mixed evenly, stirred at 90°C for 2h, and then 20 parts of the amidating agent are added, stirred and reacted at 100°C for 2h. After the reaction is completed, the amidated paraffin is obtained by condensation and separation.
[0031] Example 1
[0032] This embodiment provides a preparation process of disposable nitrile wear-resistant gloves, comprising the following steps: Step S1: adding 2.7 parts of potassium hydroxide, 1.0 parts of sulfur, 3.0 parts of zinc oxide, 1.5 parts of accelerator BZ, 0.8 parts of antioxidant CPL, 0.15 parts of modified cellulose and 0.08 parts of sodium dodecylbenzene sulfonate to 100 parts of modified nitrile rubber latex, stirring for 20 hours, adding 3.5 parts of amidated paraffin, adjusting the pH to 11.0, and obtaining a latex mixture; Step S2: Mix 22 parts of calcium nitrate, 2.0 parts of calcium stearate, 0.3 parts of tridecyl alcohol polyether-4 and 0.6 parts of a wetting agent by weight, and stir for 6 hours at a stirring speed of 20 r / min to obtain a coagulant; Step S3: placing the mold in the coagulant at 60° C. for a first dipping treatment, drying at 125° C. for 1 hour, and then placing the mold in the latex mixture for a second dipping treatment; Step S4: The mold that has completed the second dipping treatment is vulcanized in a 135° C. vulcanization oven for 20 minutes, and then passivated using a chlorine lotion, and then rinsed and neutralized by chloride ions on the surface, and dried to obtain disposable nitrile wear-resistant gloves, the fingertip thickness of the gloves is 0.15 mm.
[0033] Example 2
[0034] This embodiment provides a preparation process of disposable nitrile wear-resistant gloves, comprising the following steps: Step S1: adding 2.5 parts of potassium hydroxide, 0.6 parts of sulfur, 2.0 parts of zinc oxide, 0.8 parts of accelerator EZ, 0.6 parts of antioxidant 2246, 0.05 parts of modified cellulose and 0.05 parts of sodium dodecylbenzene sulfonate to 90 parts of modified nitrile rubber latex, by weight, stirring for 15 hours, adding 2.0 parts of amidated paraffin, adjusting the pH to 10.5, and obtaining a latex mixture; Step S2: Mix 20 parts of calcium nitrate, 1.5 parts of magnesium stearate, 0.1 parts of tridecyl alcohol polyether-3 and 0.2 parts of a wetting agent by weight, and stir for 8 hours at a stirring speed of 15 r / min to obtain a coagulant; Step S3: placing the mold in the coagulant at 55° C. for a first dipping treatment, drying at 120° C. for 2 h, and then placing the mold in the latex mixture for a second dipping treatment; Step S4: The mold that has completed the second dipping treatment is vulcanized in a 130° C. vulcanization oven for 30 minutes, and then passivated using a chlorine lotion, and then rinsed and neutralized by chloride ions on the surface, and dried to obtain disposable nitrile wear-resistant gloves, the fingertip thickness of the gloves is 0.25 mm.
[0035] Example 3
[0036] This embodiment provides a preparation process of disposable nitrile wear-resistant gloves, comprising the following steps: Step S1: adding 2.6 parts of potassium hydroxide, 0.8 parts of sulfur, 2.5 parts of zinc oxide, 1.2 parts of accelerator BZ, 0.7 parts of antioxidant 3052, 0.08 parts of modified cellulose and 0.06 parts of sodium dodecylbenzene sulfonate to 95 parts of modified nitrile rubber latex, by weight, stirring for 18 hours, adding 2.5 parts of amidated paraffin, adjusting the pH to 10.8, and obtaining a latex mixture; Step S2: Mix 21 parts of calcium nitrate, 1.8 parts of calcium stearate, 0.2 parts of laureth-4 and 0.4 parts of a wetting agent by weight, and stir for 7 hours at a stirring speed of 18 r / min to obtain a coagulant; Step S3: placing the mold in the coagulant at 58° C. for a first dipping treatment, drying at 122° C. for 2 h, and then placing the mold in the latex mixture for a second dipping treatment; Step S4: The mold that has completed the second dipping treatment is vulcanized in a vulcanization oven at 132° C. for 25 minutes, and then passivated using a chlorine lotion, and then rinsed and rinsed by chloride ion surface neutralization, and dried to obtain disposable nitrile wear-resistant gloves, the fingertip thickness of the gloves is 0.18 mm.
[0037] Comparative Example 1 This comparative example provides a preparation process of disposable nitrile wear-resistant gloves, which is different from Example 1 in that commercially available nitrile rubber latex is used instead of modified nitrile rubber latex, commercially available cellulose is used instead of modified cellulose, and commercially available paraffin is used instead of amide paraffin.
[0038] Comparative Example 2 This comparative example provides a preparation process of disposable nitrile wear-resistant gloves, which is different from comparative example 1 in that modified nitrile rubber latex is used instead of commercially available nitrile rubber latex.
[0039] Comparative Example 3 This comparative example provides a preparation process of disposable nitrile wear-resistant gloves, which is different from comparative example 1 in that modified cellulose is used instead of commercially available cellulose.
[0040] Comparative Example 4 This comparative example provides a preparation process of disposable nitrile wear-resistant gloves, which is different from comparative example 1 in that amidated paraffin is used instead of commercially available paraffin.
[0041] Comparative Example 5 This comparative example provides a preparation process of disposable nitrile wear-resistant gloves, which is different from Example 1 in that commercially available nitrile rubber latex is used instead of modified nitrile rubber latex.
[0042] Comparative Example 6 This comparative example provides a preparation process of disposable nitrile wear-resistant gloves, which is different from Example 1 in that commercially available cellulose is used instead of modified cellulose.
[0043] Comparative Example 7 This comparative example provides a preparation process of disposable nitrile wear-resistant gloves, which is different from Example 1 in that commercially available paraffin is used instead of amide paraffin.
[0044] The performance of the disposable nitrile wear-resistant gloves provided in the above embodiments and comparative examples was tested, and the testing method was as follows: (1) Abrasion resistance test: Test according to the requirements of GB / T 21196.2-2007 Textiles - Determination of abrasion resistance of fabrics by the Martindale method - Part 2: Determination of specimen damage.
[0045] (2) Tensile strength test: refer to the requirements of GB / T 528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber for testing.
[0046] (3) Elongation at break test: Test according to the requirements of GB / T 528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber.
[0047] The above performance test data is shown in Table 1.
[0048] Table 1 Performance test results
[0049] From the above content, it can be seen that the present invention prepares disposable nitrile wear-resistant gloves (Examples 1 to 3) by modifying nitrile rubber latex and introducing modified cellulose and amide paraffin. The wear resistance of the gloves is 217 to 220 times, the tensile strength is 34.2 to 34.7 MPa, and the elongation at break is 623.5 to 624.9%.
[0050] Compared with Example 1, the use of commercially available nitrile rubber latex to replace modified nitrile rubber latex, the use of commercially available cellulose to replace modified cellulose, and the use of commercially available paraffin to replace amide wax, the wear resistance is deteriorated, the tensile strength is reduced, and the elongation at break is reduced (Comparative Example 1); compared with Comparative Example 1, the use of modified nitrile rubber latex to replace commercially available nitrile rubber latex increases the tensile strength (Comparative Example 2); compared with Comparative Example 1, the use of modified cellulose to replace commercially available cellulose improves the wear resistance (Comparative Example 3); compared with Comparative Example 1, the use of amide wax to replace commercially available cellulose improves the wear resistance (Comparative Example 4); compared with Comparative Example 1, the use of amide wax to replace commercially available nitrile rubber latex increases the tensile strength (Comparative Example 5). Compared with Example 1, when commercially available paraffin is used to replace modified nitrile rubber latex, the wear resistance becomes better and the elongation at break is improved (Comparative Example 4); compared with Example 1, when commercially available nitrile rubber latex is used to replace modified nitrile rubber latex, the wear resistance becomes worse, the tensile strength decreases, and the elongation at break decreases (Comparative Example 5); compared with Example 1, when commercially available cellulose is used to replace modified cellulose, the wear resistance becomes worse, the tensile strength decreases, and the elongation at break decreases (Comparative Example 6); compared with Example 1, when commercially available paraffin is used to replace amide paraffin, the wear resistance becomes worse, the tensile strength decreases, and the elongation at break decreases (Comparative Example 7).
[0051] In summary, the present invention modifies nitrile rubber latex and introduces modified cellulose and amide paraffin, thereby effectively improving the wear resistance of nitrile gloves through the joint action of multiple components, and increasing the tensile strength and elongation at break.
[0052] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A process for preparing disposable nitrile wear-resistant gloves, characterized in that: The following steps are involved: Step S1: adding 2.5 to 2.7 parts of potassium hydroxide, 0.6 to 1.0 parts of sulfur, 2.0 to 3.0 parts of zinc oxide, 0.8 to 1.5 parts of accelerator, 0.6 to 0.8 parts of antioxidant, 0.05 to 0.15 parts of cellulose and 0.05 to 0.08 parts of sodium dodecylbenzene sulfonate to 90 to 100 parts of nitrile rubber latex in parts by weight, stirring for 15 to 20 hours, adding 2.0 to 3.5 parts of anti-wear agent, adjusting the pH to 10.5 to 11.0, and obtaining a latex mixture; Step S2: Mix 20-22 parts of calcium nitrate, 1.5-2.0 parts of a release agent, 0.1-0.3 parts of an alcohol ether auxiliary agent, and 0.2-0.6 parts of a wetting agent by weight, and stir for 6-8 hours at a stirring speed of 15-20 r / min to obtain a coagulant; Step S3: placing the mold in the coagulant at 55-60° C. for a first dipping treatment, drying at 120-125° C. for 1-2 hours, and then placing the mold in the latex mixture for a second dipping treatment; Step S4: vulcanize the mold that has completed the second dipping treatment in a vulcanization oven at 130-135° C. for 20-30 minutes, then use a chlorine lotion to perform a passivation treatment, then perform a chloride ion surface neutralization rinse, and dry to obtain a disposable nitrile wear-resistant glove; The nitrile rubber latex is modified nitrile rubber latex; The preparation method of the modified nitrile rubber latex comprises: adding 20 to 30 parts of carboxyl-terminated nitrile rubber to 80 to 100 parts of toluene by weight and stirring for 20 to 30 minutes, then adding 5 to 10 parts of formic acid and 4 to 8 parts of a hydrogen peroxide solution with a mass concentration of 35% at 10 to 12° C., heating to 30 to 40° C. and reacting for 1 to 2 hours, washing with deionized water to neutrality after the reaction is completed, extracting and separating a toluene layer, adding 1 to 3 parts of sulfur quantum dots to the toluene layer, stirring for 6 to 8 hours, and then rotary evaporating to obtain the modified nitrile rubber latex.
2. The preparation process of disposable nitrile wear-resistant gloves according to claim 1, characterized in that: The preparation method of the sulfur quantum dots comprises: adding 4 to 6 parts of sodium hydroxide and 3 to 5 parts of polyethylene glycol to 40 to 50 parts of deionized water by weight, stirring evenly, adding 1 to 2 parts of sulfur, stirring at 70 to 75° C. for 2 to 4 hours to obtain an orange-red solution; using a peristaltic pump to introduce air into the orange-red solution and continue to react for 20 to 24 hours, after the reaction is completed, dripping 10 to 12 parts of a 35% mass concentration hydrogen peroxide solution to react for 40 to 60 minutes, cooling to room temperature after the reaction is completed to obtain a light yellow solution, dialysis, rotary evaporation, and freeze-drying to obtain the sulfur quantum dots.
3. The preparation process of disposable nitrile wear-resistant gloves according to claim 1, characterized in that: The cellulose is modified cellulose; The preparation method of the modified cellulose comprises: adding 20 to 30 parts of cellulose to 200 to 250 parts of chloroform by weight, stirring for 2 to 4 hours under a nitrogen atmosphere, then adding 6 to 8 parts of furfurylamine and 2 to 4 parts of pyridine, stirring for 6 to 8 hours under a nitrogen atmosphere at 60 to 70° C., centrifuging to obtain a reaction product after the reaction is completed, and vacuum drying to obtain the modified cellulose.
4. The preparation process of disposable nitrile wear-resistant gloves according to claim 1, characterized in that: The anti-wear agent is amide paraffin; The preparation method of the amidated paraffin comprises: adding 3 to 5 parts of ethylenediamine to 8 to 10 parts of benzenesulfonic acid solution with a mass concentration of 20% by weight, and stirring evenly to obtain an amidating agent; mixing 80 to 100 parts of paraffin and 180 to 200 parts of toluene evenly, stirring at 80 to 90° C. for 1 to 2 hours, and then adding 15 to 20 parts of the amidating agent, stirring and reacting at 95 to 100° C. for 2 to 4 hours, and after the reaction is completed, condensing and separating to obtain the amidated paraffin.
5. The process for preparing disposable nitrile wear-resistant gloves according to claim 1, characterized in that: The accelerator is accelerator BZ or accelerator EZ.
6. The process for preparing disposable nitrile wear-resistant gloves according to claim 1, characterized in that: The antioxidant is selected from any one of antioxidant CPL, antioxidant 2246, and antioxidant 3052, or a combination of at least two of them.
7. The process for preparing disposable nitrile wear-resistant gloves according to claim 1, characterized in that: The release agent is calcium stearate or magnesium stearate.
8. The process for preparing disposable nitrile wear-resistant gloves according to claim 1, characterized in that: The alcohol ether auxiliary agent is selected from any one of tridecyl alcohol polyether-4, tridecyl alcohol polyether-3, and laureth-4, or a combination of at least two thereof.
9. The process for preparing disposable nitrile wear-resistant gloves according to claim 1, characterized in that: The fingertip thickness of the disposable nitrile wear-resistant gloves is 0.15-0.25 mm.
10. A disposable nitrile wear-resistant glove, characterized in that: Prepared according to the process according to any one of claims 1 to 9.
Citation Information
Patent Citations
A method for preparing nitrile gloves
CN106397894B
Nitrile glove and preparation method thereof
CN110372893A
Butyronitrile gloves and forming process thereof
CN113683825A
Quantum dot and quantum dot-containing composition
JP2018120134A
Cited By
Bipyridine bisamide organic ligand for regulating soil urease activity and inhibiting nitrification and preparation method thereof
CN119684065A